2008
DOI: 10.1103/physrevlett.101.084302
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Sound Screening in Perforated Plates

Abstract: We report extraordinary effects in the transmission of sound through periodically perforated plates, supported by both measurements and theory. In agreement with recent observations in slit arrays [M. H. Lu et al. Phys. Rev. Lett. 99, 174301 (2007)], nearly full transmission is observed at certain resonant frequencies, pointing out at similarities of the acoustic phenomena and their optical counterpart. However, acoustic screening well beyond that predicted by the mass law is achieved over a wide range of wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
122
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 26 publications
7
122
1
Order By: Relevance
“…This discrepancy originates in the effect of finite impedance ratio between the plate and the fluid. 18,19 The transmission spectrum for t = 5 mm follows quite closely the prediction of the hard-solid model.Differences between square and triangular lattices can be clearly seen by comparing their respective spectra. The positions of the Wood anomaly ͑vertical arrows in Fig.…”
supporting
confidence: 49%
See 3 more Smart Citations
“…This discrepancy originates in the effect of finite impedance ratio between the plate and the fluid. 18,19 The transmission spectrum for t = 5 mm follows quite closely the prediction of the hard-solid model.Differences between square and triangular lattices can be clearly seen by comparing their respective spectra. The positions of the Wood anomaly ͑vertical arrows in Fig.…”
supporting
confidence: 49%
“…The transmission is dipped right at the Wood anomalies. 19 Comparison between results obtained for both lattices leads to the following conclusions:…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Estrada et al [16] reported that periodically perforated aluminium plates immersed in water can achieve lower ultrasonic transmission values than homogeneous plates. The influence of the filling fraction of holes and the lattice geometry in the transmission properties has also been studied [17,18].…”
Section: Introductionmentioning
confidence: 99%